Clinical and pathological manifestations of human henipavirus infection. - Wong, K.T. (2012)
The clinicopathological features of human Nipah virus and Hendra virus infections appear to be similar. The clinical manifestations may be mild, but if severe, includes acute encephalitic and pulmonary syndromes with a high mortality. The pathological features in human acute henipavirus infections comprise vasculopathy (vasculitis, endothelial multinucleated syncytia, thrombosis), microinfarcts and parenchymal cell infection in the central nervous system, lung, kidney and other major organs. Viral inclusions, antigens, nucleocapsids and RNA are readily demonstrated in blood vessel wall and numerous types of parenchymal cells. Relapsing henipavirus encephalitis is a rare complication reported in less than 10% of survivors of the acute infection and appears to be distinct from the acute encephalitic syndrome. Pathological evidence suggests viral recrudescence confined to the central nervous system as the cause.